Efficacy of endoscopic argon gas cauterization for piriform sinus fistula during infection - Chen Xu; Xian-min Xiao; Shan Zheng; Kui-ran Dong; Kai Li; Gong Chen (Elsevier, 2022)
Background and objectives: Piriform sinus fistula (PSF) is commonly managed by surgery in quiescent inflammation, while medical conditions are hard to be stabilized in patients suffering from recurrent infections. This research attempts to discuss the diagnostic and therapeutic strategies for PSF in acute inflammation. Methods: We retrospectively analyzed the medical records of 113 patients with PSF. Presence of infection within 4 weeks before the operation was taken as a reference to divide the cases into the operation group without infection (Group A) and with infection (Group B). Results: There were 75 cases in Group A and 38 cases in Group B, with an average onset age of 8.16 (5.25-11.58) and 5.63 (4.00-9.54) years, respectively. Esophageal barium swallow identified a positive predictive value of 98.2% in Group A and 100% in Group B. Endoscopic argon gas cauterization was performed in 19 cases (19/75) in Group A, a combination with peripheral doxycycline injection in 42 cases (42/75) and endoscopic- assisted fistulectomy in 14 cases (14/75), compared to 14 cases (14/38), 16 cases (16/38) and 8 cases (8/38) respectively in Group B. The overall recurrence rate was 29.3% in Group A, while those in Group B was 36.8%. Bacterial culture of pus mainly grew Streptococcus in both groups. Conclusion: There was no significant difference in the recurrence rate by EAGC in patients with or without acute infections, and the addition of local doxycycline injection may lead to a decrease of the recurrence rate. Additionally, patients who were complicated with thyroid abscess suffered from a relatively high recurrence rate, requiring specific treatment.